ChemInform Abstract: Alphabet‐Inspired Design of (Hetero)Aromatic Push—Pull Chromophores. Issue 42 (September 2016) - Klikar, Milan; Solanke, Parmeshwar; Tydlitat, Jiri; Bures, Filip
Abstract: Review: [105 refs.